The omicron variant of SARS-CoV-2 drove broadly increased seroprevalence in a public university setting. - Ching-Wen Hou; Stacy Williams; Guillermo Trivino-Soto; Veronica Boyle; David Rainford; Selina Vicino; Mitch Magee; Yunro Chung; Joshua LaBaer; Vel Murugan (PLOS Global Public Health, 2025)
Omicron is the comparatively most transmissible and contagious variant of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). We conducted a seroprevalence study from March 1-3, 2022, to investigate the seroprevalence of SARS-CoV-2 antibodies among individuals aged 18 years and older after the Omicron outbreak. The seroprevalence of anti-receptor binding domain (RBD) antibodies was found to be 96.3% (95% CI 95.2-97.2%) compared to 88.2% (95% CI 86.1-90%) in our previous serosurvey. For anti-nucleocapsid (NC) antibodies, the seroprevalence was 39.1% (95% CI 36.6-41.7%) compared to 19.7% (95% CI 17.5-22.2%) earlier. Individuals that experienced breakthrough infections exhibited the highest levels of anti-RBD antibodies. Additionally, saliva samples showed promise as a potential diagnostic biofluid for measuring antibody levels, as they exhibited a strong agreement with the data obtained from serum samples. The near doubling of anti-NC reactivity, a proxy for history of infection, reflects the contagiousness of the omicron variant, but may also have been influenced by a more relaxed approach to precautions in the spring of 2022. Serosurveys repeated at regular intervals monitor the trend of infections in the community, delineate the geographical spread of the infection, and may guide containment measures in communities, and prompt response to future outbreaks.